2017
DOI: 10.1007/s00702-017-1747-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance correlates with the degree of dopaminergic degeneration in the associative part of the striatum in non-demented Parkinson’s patients

Abstract: Parkinson's disease (PD) patients show cognitive deficits that are relevant in terms of prognosis and quality of life. Degeneration of striatal dopaminergic afferents proceeds from dorsal/caudal to anterior/ventral and is discussed to account for some of these symptoms. Treatment with dopamine (DA) has differential effects on cognitive dysfunctions, improving some and worsening others. We hypothesized that cognitive performance during the dopaminergic OFF state correlates with DAT availability in the associati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Executive and attentional functional deficits are well described in PD patients [33][34][35][36][37]. Nevertheless, a recent study reports that executive dysfunction might be ameliorated by dopamine, whereas global cognitive deficits were not improved [38]. Since we examined all patients in the on state, executive function might be even underestimated in our cohort.…”
Section: Association Of Mds-updrs Mocamentioning
confidence: 91%
“…Executive and attentional functional deficits are well described in PD patients [33][34][35][36][37]. Nevertheless, a recent study reports that executive dysfunction might be ameliorated by dopamine, whereas global cognitive deficits were not improved [38]. Since we examined all patients in the on state, executive function might be even underestimated in our cohort.…”
Section: Association Of Mds-updrs Mocamentioning
confidence: 91%
“…Instead, subdivision based on the connectivity between the basal ganglia and the neocortex can be used, where the striatum is divided into a limbic, associative, and sensorimotor striatum (respectively ventral striatum, caudate and ventrolateral putamen, and dorsolateral putamen) [14]. The functional regions have shown to be useful for molecular imaging studies examining correlations with behavioral and clinical outcome measures [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, dopaminergic medication improves certain cognitive functions—verbal fluency, working memory, visuospatial function and executive function—in PD patients 12‐16 . FP‐CIT studies showed a correlation between striatal FP‐CIT uptake and cognitive function—primarily executive and visuospatial function—in PD patients 17‐22 …”
Section: Discussionmentioning
confidence: 99%
“…Striatal FP‐CIT binding correlated with attention/working memory, executive and visuospatial function in de novo PD patients with and without MCI 20 . Global cognitive function correlated with striatal FP‐CIT binding in non‐demented PD patients 21 . Striatal FP‐CIT binding also correlated with frontal, executive and visuospatial function in patients with advanced PD and MCI 22 .…”
Section: Introductionmentioning
confidence: 92%